Resin-loaded heterogeneous polyether sulfone ion exchange membranes for saline groundwater treatment - Mudau, Fulufhelo H.; Motsa, Machawe M.; Hassard, Francis; De Kock, Lueta-Ann (MDPI, 2022)
Arid areas often contain brackish groundwater that has a salinity exceeding 500 mg/L. This poses several challenges to the users of the water such as a salty taste and damage to household appliances. Desalination can be one of the key solutions to significantly lower the salinity and solute content of the water. However, the technology requires high energy inputs as well as managing waste products. This paper presents the fabrication of ultrafiltration heterogeneous ion exchange membranes for brackish groundwater treatment. Scanning electron microscopy (SEM) images showed a relatively uniform resin particle distribution within the polymer matrix. The mean roughness of the cation exchange membrane (CEM) and anion exchange membrane (AEM) surfaces increased from 42.12 to 317.25 and 68.56 to 295.95 nm, respectively, when resin loading was increased from 1 to 3.5 wt %. Contact angle measures suggested a more hydrophilic surface (86.13 to 76.26° and 88.10 to 74.47° for CEM and AEM, respectively) was achieved with greater resin loading rates. The ion exchange capacity (IEC) of the prepared membranes was assessed using synthetic groundwater in a dead-end filtration system and removal efficiency of K+, Mg2+, and Ca2+ were 56.0, 93.5, and 85.4%, respectively, for CEM with the highest resin loading. Additionally, the anion, NO3− and SO42− removal efficiency was 84.2% and 52.4%, respectively, for the AEM with the highest resin loading. This work demonstrates that the prepared ultrafiltration heterogeneous ion exchange membranes have potential for selective removal for of ions by ion exchange, under filtration conditions at low pressure of 0.05 MPa.
Keywords: heterogeneous ion exchange membranes; ultrafiltration; ion exchange resin loading; ion exchange capacity; groundwater treatment; salt rejections